Perangkat Teknologi Digital Sebagai Media Simulasi Try Out Di Tingkat Sekolah Menengah Pertama - Astuti, Arin Yuli; Sari, Dyah Mustika; Novawati, Nunung Rohmatun (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
Today's digital technology is needed for daily needs. Everything that is processed and processed from resources can be solved with digital technology. Utilizing digital technology will save more costs than using it manually. In addition to downsizing the utilization of digital technology will also speed up the process and results of what is needed. The development of digital technology is currently very rapid, even from the world of education has implemented digital technology for learning. IT Ma'arif Bandar Pacitan Middle School is a private school that just took a computer-based exam in 2018. The test was carried out to join other schools. Ma'arif Bandar IT Middle School is a pilot private junior high school that has developed quite rapidly. However, due to lack of funds to have their own system, the try out practice exam still joins other schools. The researcher tries to make an application where students can run Try Out exams or practice exams independently. The research method for designing a tryout system is to use the Website Design Method (WSDM) method. The website design methodology was created to provide a systematic and scientific approach to website design. This application can later be used on computers or mobile phones. Utilization of digital technology using the Try Out application can benefit students and the school. In addition to using the official application from the government, the school and students can learn on their own by using this application.